Audit Selection in the European Football Industry under Union of European Football Associations Financial Fair Play - Dimitropoulos, Panagiotis (International Journal of Economics and Financial Issues, 2016)
The scope of this study is to examine the characteristics of football clubs that choose a high quality auditor and whether this audit selection process was different before and after the implementation of UEFA's Financial Fair Play Regulation (FFP). The study employs a sample of 109 European football clubs for a seven-year period, 2008-2014 (three years before and four years after regulatory intervention), to investigate the impact of this regulatory intervention upon the decision of clubs to hire a big-4 audit firm. The study demonstrates that after FFP implementation, profitability and cash flows became highly significant factors urging clubs to select a big-4 audit firm in order to signal to the market and the regulators that they are able to achieve the regulatory requirements. UEFA should take into consideration that, the imposition of regulatory monitoring tied to accounting data may lead to adverse behavior on behalf of the clubs, thus reducing the effectiveness of the new regulation. Keywords: Audit quality, Audit selection, European football clubs, Financial fair play. JEL Classification: M41, M42